BUKU PEMBELAJARAN HURUF JEPANG HIRAGANA MELALUI ILUSTRASI - PANJI SUSANTO, Dr. Syafwandi, M.Sn., Henra Afriwan, S.Sn., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
The purpose of designing this hiragana letters learning books is to produce an icon design that is tailored to the target audience and to design an effective and efficient alternative learning media. The design background is the difficulty of students in remembering and writing Hiragana letters. Therefore we need a learning book design as an alternative learning media. Visual communication strategies used to provide memory and picture clues can contribute to improving memory. The design method used is the glass box method, where in this method the design process can be measured transparently and rationally. The selection of book media as this final work. The approach used in design is 5W + 1H (What, Who, Why, When, Where, How). The method used in collecting data is through observation, interviews, and documentation. The main media in the form of learning books, coupled with supporting media as promotions such as notebooks, X-Banners, Stickers, Posters, Pens, T-shirts, and Totebag.Keywords : Book, Japan, Hiragana, Ilustrations.